The states of sulfate groups affect the mechanical and separation properties of carboxymethyl cellulose/chitosan complex membranes. Issue 31 (10th March 2016) - Wu, Jia-Kai; Wang, Xue-San; Chen, Kai-Fan; Zhou, Guo-Jun; Li, Xia; Xu, Jian; An, Quan-Fu
Abstract : Two states of sulfate groups were dissected to affect mechanical and separation performances of PECMs prepared from CS and CMC. Abstract : Solution-processable polyelectrolyte complexes (PECs) were fabricated from sulfonated carboxymethyl cellulose (SCMC) and chitosan (CS) by two methods. Two states of sulfate groups (SO3 − ) in PECs, i.e., complexed and free sulfate groups, were distinguished and shown to play important roles in determining mechanical properties and separation performances of PEC membranes (PECMs). PECMs containing different states of SO3 − were subjected to pervaporation dehydration, and their hydrophilic properties and swelling behaviors were thoroughly discussed. It was found that the tensile strength of PECMs could be effectively enhanced by increasing the ratio of complexed SO3 − groups, while the hydration and flexibility were modulated by free SO3 − groups. In the dehydration of water–ethanol mixtures, both the flux and selectivity of PECMs were simultaneously improved through the incorporation of SO3 − groups, whereby the improved pervaporation performance was mainly attributed to the free SO3 − groups.